Analyzing Academic Attainment Among Students in Government and Non-Government Schools Based on Geographical Context - Anuradha R. (International Journal of Education Sciences, 2024)
This paper has attempted to determine the level of education attained by students in Maharashtra state's government and non-government schools in relation to their locality to investigate the methodical distinctions between the two categories of schools—urban and rural. Students attending non-government schools outperform those attending government schools in terms of academic achievement. 200 boys and girls in the 9th and 10th grades, 120 from the urban region and 80 from the rural area, selected by random sampling from government and non-government schools in the state of Maharashtra. Students took the Self-made Educational Achievement Test Forms A and B. For the study, the survey method was employed. The data has been analyzed using suitable statistical techniques, such as the t-test, mean, and standard deviation. Based on data analysis, it was discovered that pupils in urban areas score better academically than those in rural areas. This study examines students' academic performance in both government and non-government schools, highlighting the impact of geographic location on learning results. The goal of the research is to offer a thorough understanding of the elements causing educational gaps and to pinpoint viable remediation tactics. The purpose of the paper is to present a thorough understanding of the causes causing educational inequality by highlighting the impact of geographic location on educational results. Additionally, it looks for workable solutions to close these disparities and raise educational fairness in various geographical areas.
Keywords: Academic Achievement; Academic Attainment; Educational Gaps; Government Schools; Non-Government Schools